Case Report: Allelic and biallelic variants in coagulation factor XI cause factor XI deficiency - Liang, Chen; Jin, Jie-Yuan; Shi, Hai-Hong; Li, Hao-Xian; Chen, Lin-Lin; Zhang, Yang-Hui; Wang, Qin; Li, Qiu-Li; Li, Rui-Man (Frontiers in Cardiovascular Medicine, 2024)
Factor XI deficiency is a rare inherited coagulation disorder with an estimated prevalence of affecting 1 in 1 million. It is characterized by mild and variable bleeding phenotypes, including bruises, nosebleeds, hematuria, and postpartum hemorrhage. It can be caused by either allelic or biallelic variants in coagulation factor XI (F11). Coagulation factor XI is a glycoprotein that circulates in plasma as a non-covalent complex with high-molecular-weight kininogen. It is converted to an active protease, coagulation factor XIa, which participates in blood coagulation as a catalyst. In this study, we recruited a family with Factor XI deficiency and identified two F11 variants using whole-exome sequencing. One (NM_000128.4: c.841C>T, p.Q281X) was a known variant, and the other (NM_000128.4: c.1832T>G, p.V611G) had not been reported. In addition, we compiled the characteristics of known missense variants in coagulation factor XI. Our findings enriched the variant spectrum of Factor XI deficiency and contributed to the genetic counseling and molecular diagnostics of Factor XI deficiency.